Zebrafish as a model to study inflammation: A tool for drug discovery - Belo, Marco A.A. [UNESP]; Oliveira, Melque F.; Oliveira, Susana L. [UNESP]; Aracati, Mayumi F. [UNESP]; Rodrigues, Letícia F. [UNESP]; Costa, Camila C. [UNESP]; Conde, Gabriel [UNESP]; Gomes, Juliana M.M.; Prata, Mariana N.L.; Barra, Ayslan; Valverde, Thalita M.; de Melo, Daniela C.; et al. (Elsevier, 2021)
This study aims to demonstrate the applicability and importance of zebrafish (Danio rerio) model to study acute and chronic inflammatory responses induced by different stimuli: carrageenan phlogogen (nonimmune); acute infection by bacteria (immune); foreign body reaction (chronic inflammation by round glass coverslip implantation); reaction induced by xenotransplantation. In addition to the advantages of presenting low breeding cost, high prolificity, transparent embryos, high number of individuals belonging to the same spawning and high genetic similarity that favor translational responses to vertebrate organisms like humans, zebrafish proved to be an excellent tool, allowing the evaluation of edema formation, accumulation of inflammatory cells in the exudate, mediators, signaling pathways, gene expression and production of specific proteins. Our studies demonstrated the versatility of fish models to investigate the inflammatory response and its pathophysiology, essential for the successful development of studies to discover innovative pharmacological strategies.
Keywords: Acute and chronic inflammation; Foreign body reaction; Inflammatory reaction; Innate Immunity; Teleost fish; Xenotransplantation